Enhancing inventory accuracy in dairy industries - Francisco Tiago Araújo Barbosa; Maria Silene Alexandre Leite; Mauro Sergio Carneiro Mascarenhas; Rogerio Santana Peruchi (Brazilian Journal of Operations & Production Management, 2025)
Goal: The goal is to analyze the application of Lean Six Sigma and DMAIC in the inventory management of a dairy industry, aiming to optimize inventory accuracy, reduce picking errors, and enhance OTIF performance, thereby improving overall operational efficiency.